TEACHING MATERIALS IN SOCIOLOGY LEARNING FROM VARIOUS VARIABLES IN HIGH SCHOOL - Mila Noviana; Jepri Utomo (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
This study aims to determine the presentation of Sociology teaching materials during the Covid-19 pandemic seen from various variables (gender, class, age, school location, and school status) in high school. The research uses a survey type quantitative approach. The population in this study were all high school students in Central Lombok district. The sampling technique was accidental sampling with a sample of 450. The data on the presentation of learning materials was collected with the help of google forms which had met the research requirements. All data were analyzed quantitatively using comparative analysis, namely non-parametric statistics, did not meet the analysis requirements. The results showed that the presentation of teaching materials tended to be contextual as seen in the indicators of facts, concepts, principles, and procedures during the Covid-19 pandemic, and there were differences in perceptions regarding the presentation of teaching materials from the variables of school location and school status while the variables of gender, age, and There are no differences in the class presentation of teaching materials during the Covid-19 pandemic. Therefore, the presentation of teaching materials during the Covid-19 pandemic should consider geographical characteristics (gender, age, class, school location, school status) in instructional design interventions.